2022
DOI: 10.3390/fishes7040151
|View full text |Cite
|
Sign up to set email alerts
|

Investment Feasibility Analysis of Large Submersible Cage Culture in Taiwan: A Case Study of Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum)

Abstract: Onshore farming for premium aquaculture is under scrutiny and criticism partially due to possible causes of adverse environmental impacts on other resource users and the surrounding environment. The best alternative to preventing or minimizing these impacts is to utilize open seawater by large submersible cage culture. The current operation in Taiwan has demonstrated that the culture operation is technically feasible but economically demanding because of high capital and operating costs. Therefore, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The pay-back period of 4 years in local model cages from investment A is encouraging and shows that tilapia cage aquaculture can provide a significant return on investment. These results corroborate the findings of Lan et al 16 , who report a pay-back period of 3.55 years for 24-unit large submersible cage aquaculture in Taiwan. benefit-cost ratio greater than one, equal to one, or less than one indicates profit, break-even, or loss, respectively 17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The pay-back period of 4 years in local model cages from investment A is encouraging and shows that tilapia cage aquaculture can provide a significant return on investment. These results corroborate the findings of Lan et al 16 , who report a pay-back period of 3.55 years for 24-unit large submersible cage aquaculture in Taiwan. benefit-cost ratio greater than one, equal to one, or less than one indicates profit, break-even, or loss, respectively 17 .…”
Section: Discussionsupporting
confidence: 92%
“…These results however differ from the findings of Otubusin and Olaitan 18 , who report 34.10 and 53.34% RRI in small-scale tilapia farming in floating net cages from Lake Kainji, Nigeria. Also, Lan et al 16 found a higher profit index of 2.15 for Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum) in large submersible cage cultures in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work [24], with Snubnose Pompano as the target fish species, we proposed an approach to analyze the investment feasibility analysis of large submersible cage culture in Taiwan. The research findings show that large submersible cage culture is financially profitable when the number of operation units are larger than 8.…”
Section: Discussionmentioning
confidence: 99%
“…Although it offers the advantage of mitigating the risk of fish mortality and adverse environmental impacts, it is constrained by substantial capital investments and operational costs. In a prior study [24], we conducted an economic analysis of large submersible cage culture, focusing on snubnose pompano (Trachinotus anak) and cobia (Rachycentron canadum) as target fish species. The study demonstrated that large submersible cage culture can be financially viable with an increase in the number of operational units.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture is gradually being extended to open‐cage marine waters to meet the increasing demands. However, achieving maximum production has proven difficult because of several challenges (physical, chemical, and biological) that contribute to decreased fish production, with diseases caused by infectious agents being the most detrimental worldwide (Gnanagobal & Santander, 2022; Lan et al, 2022; Pridgeon & Klesius, 2012). In humid subtropical regions (Dawadi et al, 2023) the Lactococcus genus of gram‐positive bacteria is most prominent (Kang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%